National Innovation System of Israel at the Beginning of the 21st Century - I. G. Korotkov (Мир новой экономики, 2020)
Difficult geopolitical circumstances and natural resources scarcity laid down the vector of science and technology development of Israel. The only “natural resource” that was and still is in plenty — high-qualified human resource. As for today, Israel takes the first place in the world having its state support of public R&D as a per cent of GDP (4.5 per cent), the number of startup companies concerning population and quantity of researchers. Russia is interested in Israeli experience in the formation of a national innovation system (NIS) because of the same high state influence on the economics in this country. Powers of the state in Israel through the agency of the Office of the Chief Scientist (OCS) stimulate a wide variety of applied R&D and upon that do not prescribe the market how to develop but use targeted funding and state programs to reward the development of priority branches. In Russia, as opposed to Israel, the powers of state aim to play a vital role in chosen market segments, therefore suppressing the development of small enterprises. If in Israeli innovation economics the central place is occupied by the startup companies, in Russia, in the opposite, at the innovation market dominate the massive state-owned enterprises, restraining innovation processes that shift into low gear without business initiative. Israeli experience can be used in such innovation economics’ sectors as state support of innovations; technology transfer organization; commercialization of technologies, elaborated in Research and Development Establishment and universities; formation of international scientific and technological cooperation system; using of dual technologies; training of innovation managers.